Faces of Muhammad : Western perceptions of the prophet of Islam from the Middle Ages to today - Tolan, John Victor, 1959- (Princeton University Press, 2019)
In European culture, Muhammad has been vilified as a heretic, an impostor, and a pagan idol. But these aren’t the only images of the Prophet of Islam that emerge from Western history. Commentators have also portrayed Muhammad as a visionary reformer and an inspirational leader, statesman, and lawgiver. In Faces of Muhammad, John Tolan provides a comprehensive history of these changing, complex, and contradictory visions. Starting from the earliest calls to the faithful to join the Crusades against the “Saracens,” he traces the evolution of Western conceptions of Muhammad through the Reformation, the Enlightenment, and the nineteenth and twentieth centuries, and up to the present day.--